2017
DOI: 10.21595/jve.2016.17324
|View full text |Cite
|
Sign up to set email alerts
|

Research on modeling and dynamic characteristics of complex coaxial rotor system

Abstract: Abstract. To make up deficiency of the finite element method in predicting nonlinear dynamic characteristics of coaxial rotor systems, nonlinear dynamic model of a coaxial rotor system was established with a method combining the finite element method and the fixed interface modal synthesis method. Then an implicit time domain method was presented to solve the nonlinear equations of motion thus dynamic characteristics of the rotor system can be obtained. The computational efficiency of this method largely depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The inertia matrix, damping matrix, gyrscopic matrix and stiffness matrix of the rotor system shown in Fig. 4 are established with Timoshenko beam theory [14]. At the same time, the effect of the cross stiffness caused by the Alford force at the impeller and the turbine are considered.…”
Section: Resultsmentioning
confidence: 99%
“…The inertia matrix, damping matrix, gyrscopic matrix and stiffness matrix of the rotor system shown in Fig. 4 are established with Timoshenko beam theory [14]. At the same time, the effect of the cross stiffness caused by the Alford force at the impeller and the turbine are considered.…”
Section: Resultsmentioning
confidence: 99%
“…The unbalanced force F e [19,20] established a dynamic model of a rotor-bearing system with intermediate bearings; they calculated the critical speeds and vibration modes of the system and verified them with a single-rotor test system, but the established analysis model did not consider nonlinear factors. Wang et al [21] established a rotor-bearing model that considered intermediate bearings and nonlinear SFD characteristics, and they carried out a rotor-bearing test to verify their proposed model-ing and analysis methods; their research results indicated that it is feasible to build a complex dual-rotor-bearing system with SFDs and bearings using Timoshenko beam elements. The FE modeling method using Timoshenko beam elements has now developed into an effective method for establishing dynamic models of complex rotor-bearing and whole-engine systems in aeroengines with nonlinear characteristics.…”
Section: Responses Of the Turbine Shared Support Rotorbearing Systemmentioning
confidence: 99%
“…The mass matrix m e , stiffness matrix k e , and gyroscopic matrix g e of the shaft segment are given in Equations ( 2)-( 5), the derivations of which are given elsewhere [21].…”
Section: Dynamic Model Of Rotor-bearing Systemmentioning
confidence: 99%
“…The mass matrix e m , stiffness matrix e k , and gyroscope matrix e g of the shaft segment are given in Eqs. ( 2)-( 5), the derivations of which are given elsewhere [21]:…”
Section: Introductionmentioning
confidence: 99%